Squandered Opportunity, but also Noticeable Effort (Czech Journal of International Relations, 1999)
Ralf Gebel: „Heim ins Reichl“ Konrad Henlein und der Reichsgau Sudetenland (1938-1945). Veroffentlichungen des Collegium Carolinum, Band 83. R. Oldenburg Verlag, München 1999, 425 stran.